Examining the knowledge level of nurses regarding aseptic non touch technique in nurses: a cross-sectional study - Yilin Chen; Xiuzhu Cao; Chang Liu; Wanting Sheng; Jie Wang; Linfang Zhao (BMC, 2024)
Abstract Background Healthcare-associated infections (HAIs) are important indicators of healthcare quality. The aseptic non touch technique (ANTT), a standardised aseptic technique, is a crucial preventative measure against HAIs. However, there is insufficient evidence currently available regarding ANTT awareness and proficiency among nurses. This study aimed to investigate the status of ANTT proficiency in a cohort of nurses and analyse the associated risk factors, with the ultimate goal of providing a reference for promoting the application of ANTT in clinical practice. Methods The study population was sampled from nurses working in a tertiary hospital in Zhejiang Province, China, in January 2024. A cross-sectional survey was conducted using a self-designed questionnaire to assess ANTT knowledge. Multivariate linear regression analysis was used to analyse the risk factors influencing ANTT knowledge in nurses. Results A total of 458 nurses were included in this study. The cohort had an overall score of 49.7% correct responses on the ANTT knowledge questionnaire, with a mean score of 12.4 ± 2.4 out of 25, and 30.1% of the nurses felt that they did not need training related to ANTT. Multivariate linear regression analysis indicated that professional title, educational level, and the need for ANTT training were independently associated with ANTT knowledge in nurses. Nurses with Master's degrees and associated chief nurses were observed to have higher levels of ANTT knowledge compared to the rest. Conclusions ANTT knowledge is insufficient among nurses in China, and its importance is not widely recognised. Continuous efforts are required to strengthen this knowledge. Constructing sustained, multiform, and stratified training programmes may represent an effective method to strengthen ANTT knowledge among nurses and promote its clinical use.